Attitude and potential benefits of modern information and communication technology use and telemedicine in cross-sectoral solid organ transplant care - Martin Holderried (Nature Portfolio, 2021)
Abstract Situations like the COVID-19 pandemic urgently require the implementation of eHealth for vulnerable patient populations. Here we quantitatively evaluate use and potential of modern information and communication technology (ICT) in solid organ transplant (SOT) recipients. We conducted a structured, questionnaire-based, cross-sectional study that was addressed to patients after kidney, liver, pancreas, or combined transplantation. We focused on: sociodemographic data, present use of digital technologies in daily life and for health reasons, patients’ eHealth literacy, and their overall attitude towards eHealth. A total of 234 patients completed the questionnaire. Most of the patients (90%) have a web-enabled computer, 78.2% have a smartphone, and 71.8% regularly search the internet for health-related information. Sixty-eight percent would like to receive discharge summaries online, and 54% would like to chat online with their physicians. Even though ICT use in daily life was age-related, no significant difference could be shown for health reasons or the type of transplanted organ. Modern ICT use is predominantly accepted for health reasons by SOT recipients. Regardless of the transplanted organ, a deeper integration of eHealth has potential for improving cross-sectoral care. To successfully implement eHealth technologies in cross-sectoral care future research should include online physician–patient communication, data security, data safety, and the aspects of quality and safety of care.